2015
DOI: 10.15379/2408-9834.2015.02.01.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Isomerization Activity and Aromatization Activity in Catalytic Naphtha Reforming over Tri-Metallic Modified Catalyst using Design of Experiment Based on Central Composite Design and Response Surface Methodology

Abstract: In this work, the estimation capacity of the response surface methodology (RSM), in the catalytic naphtha reforming to enhance the octane number of reformats via isomerization reaction pathway and minimize the aromatization activity over tri-metallic modified Pt-Re/Al2O3 catalyst were investigated by applying Design of experiment (DOE). The parent bimetallic catalysts were modified using a relatively inactive metal (Sn) by means of employing non-conventional method of anchoring technique called controlled surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The study was done over three reaction variables, namely, temperature, pressure and space velocity (LHSV) using design of experiment based on central composite design and RSM. The results present that the optimum conditions to obtain minimum aromatization activity (20%), maximum isomerization activity (58%), and RON (89) are equal to T = 460°C and P = 35 bar, P = 30 bar, and LHSV = 1.8 h, and 449.9°C, 32 bar and 1.7 h −1 , respectively 13 …”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The study was done over three reaction variables, namely, temperature, pressure and space velocity (LHSV) using design of experiment based on central composite design and RSM. The results present that the optimum conditions to obtain minimum aromatization activity (20%), maximum isomerization activity (58%), and RON (89) are equal to T = 460°C and P = 35 bar, P = 30 bar, and LHSV = 1.8 h, and 449.9°C, 32 bar and 1.7 h −1 , respectively 13 …”
Section: Introductionmentioning
confidence: 98%
“…The results present that the optimum conditions to obtain minimum aromatization activity (20%), maximum isomerization activity (58%), and RON (89) are equal to T = 460 C and P = 35 bar, P = 30 bar, and LHSV = 1.8 h, and 449.9 C, 32 bar and 1.7 h À1 , respectively. 13 In 2016, Elfghi evaluated a quadratic polynomial equation of RSM model in catalytic naphtha reforming over bi-functional Pt-Re-S/ Al 2 O 3 Cl catalysts. The results demonstrated that two variables of the reaction temperature and pressure have the greatest effect on naphtha reforming.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of a pilot plant performance for catalytic naphtha reforming is complicated because of the competing of varies successive reactions taking place subsequently such as dehydrogenation and dehydroisomerization of naphthenes to aromatics, dehydrogenation of paraffins to olefins, dehydrocyclization of paraffins and olefins to aromatic, isomerization or hydroisomerization to isoparaffins, isomerization of alkylcyclopentanes, and substituted aromatics and hydrocracking of paraffins and naphthenic to lower invaluable hydrocarbons [16,17]. The above subsequent/successive reactions occurred because the composition of the real feedstock is sophisticated and very complex as it contains hundreds of hydrocarbons, hence, the use of model compound as a reactant feed is highly recommended as well as the development and adaptation of detailed experimental procedures using Design of Experiment (DOE) approach based on Central Composite Design (CCD) technique coupled with different modeling and optimization tools such as RSM and ANN are extremely important in order to attain reliable data [18][19][20].…”
Section: Introductionmentioning
confidence: 99%